2021
DOI: 10.4274/jcp.2021.0029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Health Care-Related Infections in Pediatric and Newborn Intensive Care Units in A University Hospital: The Seven-Year Retrospective Study

Abstract: Ünitesinde (YDYBÜ) saptanan Sağlık Bakımı İlişkili Enfeksiyonların (SBİE) insidansı, dansitesi ve karşılıklı ilişkilerinin genel bir durum tespiti çerçevesinde değerlendirilmesi amaçlandı. Gereç ve Yöntem: Bu çalışmada Hastalık Kontrol ve Korunma Merkezleri (CDC) 2015 ve Ulusal Hastane Enfeksiyonları Sürveyans Ağı (UHESA) 2017 kriterleri dikkate alınarak 2012 -2018 yılları arasında SBİE gelişen 91 ÇYBÜ hastası ve 158 YDYBÜ hastasının verileri retrospektif olarak incelendi. Bulgular: ÇYBÜ ve YDYBÜ de sırasıyla;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
3
1
1
Order By: Relevance
“…Similar to other studies, in the present study, the mean age of the patients cared for in the aICU was (7.4 ± 5.4) years (10)(11)(12). The length of stay in the pICU was generally between 2 and 9.7 days in previous studies; it was similarly 6.6 ± 14.2 days in the present study (13)(14)(15). The length of hospital stay was found to vary according to the inpatient profile, with 11.8 ± 17.7 days in the present study, which was different to other studies (15,16).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to other studies, in the present study, the mean age of the patients cared for in the aICU was (7.4 ± 5.4) years (10)(11)(12). The length of stay in the pICU was generally between 2 and 9.7 days in previous studies; it was similarly 6.6 ± 14.2 days in the present study (13)(14)(15). The length of hospital stay was found to vary according to the inpatient profile, with 11.8 ± 17.7 days in the present study, which was different to other studies (15,16).…”
Section: Discussionsupporting
confidence: 89%
“…The length of stay in the pICU was generally between 2 and 9.7 days in previous studies; it was similarly 6.6 ± 14.2 days in the present study (13)(14)(15). The length of hospital stay was found to vary according to the inpatient profile, with 11.8 ± 17.7 days in the present study, which was different to other studies (15,16). It is thought that the longer ICU and hospital stays recorded in the present study could be attributable to chronic comorbidities in 76.2% of the patients and the lack of a sufficient number of palliative care units and rehabilitation centres.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…11,12 In Türkiye, studies have reported HAI rates of 3.2 to 42.3%, and HAI incidence densities of 3.1 to 21.3/1,000 patient days in NICUs. 2,13 In our study, the HAIs rate was 3.4% and the incidence density was 2.68/1,000 patient days, rather lower than in other Turkish studies.…”
Section: Discussioncontrasting
confidence: 74%
“…Widely varying rates of HAI in NICUs have been reported globally (7.3-57.7%) and in Türkiye (3.2-42.3%). 1,2 The most common infections in NICUs are bloodstream infections (BSIs), pneumonia, and urinary tract infections (UTIs). Among the risk factors for HAIs are prematurity, low birth weight, mechanical ventilation, central venous catheter use, inappropriate use of broad-spectrum antibiotics, and long-term hospitalization.…”
Section: Introductionmentioning
confidence: 99%